Rancang Bangun Rangka Mesin Pencetak Pelet Kapasitas 40 Kg/ Jam - Ramadhan, Ferdyansyah Rohmatulloh; Fauzi, Ah. Sulhan (Universitas Nusantara PGRI Kediri, 2022)
Most of the residents in Mangunrejo Hamlet, Bangkok Village, Gurah District, Kediri Regency, East Java Province, cultivate catfish as one of their livelihoods. Catfish Pellet Printing Machine Capacity of 40 kg/hour can be a solution to reduce the cost of catfish cultivation so as to increase the profits obtained. In designing a catfish pellet molding machine with a capacity of 40 kg/hour, among others, planning the frame design and testing, calculating the frame, making the frame and components supported by the frame. Several processes in making the frame on a catfish pellet molding machine with a capacity of 40 kg/hour include material procurement, measurement, cutting, welding, drilling, cutting, finishing, and assembling components supported by the frame, as well as testing the frame. Based on the results of the discussion, it can be concluded that the type of frame material used is angled iron 6 meters 40 mm x 4 mm thick 3 mm with engine frame dimensions as follows: height 104 cm, width 104 cm, and length 119 cm. In addition, this frame is also able to support a variety of mixed materials that will be used to print pellets because because σtensile frame<σmax material that is 16,09 N/mm2 < 723,83 N/mm2.